Influence of temperature on the reproductive and demographic parameters of two spider mite pests of vineyards and their natural predator - Stavrinides, Menelaos; Mills, Nicholas J. (My University, 2011)
We evaluated the influence of temperature on demographic parameters of two common vineyard pests, the Pacific spider mite, Tetranychus pacificus McGregor, and the Willamette spider mite, Eotetranychus willamettei (McGregor) (Acari: Tetranychidae). Additionally, we investigated the effects of temperature on their shared predator, the western predatory mite, Galendromus occidentalis (Nesbitt) (Acari: Phytoseiidae). The intrinsic rate of increase (r (m) ) was higher for T. pacificus than E. willamettei at 15 and 28A degrees C, but similar at 22A degrees C. G. occidentalis achieved a higher r (m) than T. pacificus from 15 to 28A degrees C, but the difference was significant only at 22A degrees C. At 34A degrees C, the r (m) for both T. pacificus and G. occidentalis was negative, while E. willamettei did not develop at this temperature. Prey species did not affect demographic parameters of G. occidentalis. These results suggest that higher temperatures favor T. pacificus over the less damaging E. willamettei, and may also reduce the effectiveness of G. occidentalis.
Keywords: Eotetranychus willamettei; Galendromus occidentalis; Grapes; Life history parameters; Temperature; Tetranychus pacificus